THE CHANGING ASPECTS OF MARRIAGE RITUALS AND PRACTICES IN RURAL HARYANA: A SOCIOLOGICAL INSIGHT - Ms. Neetu; Malik, Naveen; Joginder; Kumar, Sunil (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Marriage, as a social institution, holds a pivotal role in structuring human relationships and ensuring cultural continuity. In rural Haryana, wedding rituals have historically embodied the region's deep-seated traditions and communal values. However, the dynamics of these rituals have shifted over time, reflecting broader societal transformations. Thus, keeping in view, the present study has been undertaken to know and analyse the changing aspects of weeding rituals, ceremonies and practices in rural Haryana along with the assessment of the effects on the family and the institution of marriage. The study adopts a descriptive and exploratory research framework, focusing on four districts of Haryana: Rewari, Jind, Ambala, and Sirsa. 40 male & female respondents (10 from each district) possessing 60 plus year of age were selected through purposive/convenient sampling. Data was collected by using qualitative methods, specifically through in-depth discussions and direct observations, to capture the lived experiences and insights of participants. The findings indicate a significant change in the nature and style of traditional rituals such as tail chadhana, baan, and Nyonda dalna, etc. Some of meaningful wedding ceremonies have largely been reduced to symbolic gestures or have disappeared altogether. This erosion of ritualistic depth not only marks a change in matrimonial customs but also signals a shift in the cultural fabric of rural Haryana. The study underscores the tension between cultural preservation and the forces of modernization, offering a critical reflection on the future of these fading traditions.